SYPHILIS RESURGENCE IN THE 21ST CENTURY: GLOBAL EPIDEMIOLOGICAL SHIFTS, CONGENITAL BURDEN, AND IMPLICATIONS FOR PREVENTION - Kacperczyk, Julia; Bezak, Julia; Winkler, Mateusz; Arczewska, Aleksandra; Stolarczyk, Magdalena; Jagura-Sukiennik, Aleksandra; Michałowska, Klaudia; Kolanowski, Oliwier; Zaborowski, Michał; Purgał-Zaborowska, Klaudia (International Journal of Innovative Technologies in Social Science, 2026)
Background. Syphilis is not a disease we fail to cure; it is a disease we fail to prevent. Caused by Treponema pallidum and fully susceptible to penicillin, it should not be resurging. Yet over the past decade, syphilis has re-established itself as a global public health threat, with rising incidence and a striking resurgence of congenital syphilis- an outcome that exposes systemic gaps in maternal care and surveillance.Aim. This review interprets recent global shifts in syphilis epidemiology and evaluates advances in preclinical syphilis vaccine development to clarify the prospects for future prevention.Material and methods. A narrative review was conducted using PubMed, Scopus, and MDPI databases (2015-2025), and supplemented by surveillance reports from the official websites of international agencies, including the World Health Organization (WHO), the Centers for Disease Control and Prevention (CDC), and the European Centre for Disease Prevention and Control (ECDC). Sources were selected for epidemiological relevance or substantive contributions to vaccine research.Results. Across regions, evidence consistently demonstrates sustained increase in syphilis and congenital syphilis rates. Preclinical vaccine studies have yielded promising immunogenicity and partial protection in animal models; however, no candidate has entered human trials, as key antigenic and translational barriers persist.Conclusions. The contemporary rise of syphilis reflects health-system fragility rather than therapeutic limitation. While vaccines may eventually augment prevention efforts, immediate progress depends on strengthening surveillance, ensuring universal antenatal screening, and closing the structural gaps that allow a curable infection to continue to spread.